Data from "Open Data engages Citation and Reuse: A Follow-up Study on Enhanced Publication" - Farace, Dominic; Schöpfel, Joachim (The grey journal, 2022)
The data collected is based on the responses of forty-four authors/researchers, who have presented full-text papers published in the International Conference Series on Grey Literature. The dataset consists of responses to ten questions, two of which are open-ended. Six of the questions are taken from a questionnaire carried out in 2011 within GreyNet's Enhanced Publications Project. The data contain the number of responses and percentages to each question. The questions deal with the author's own empirical research data, its availability, the formats in which it appears, and the author's willingness to archive it and make it openly accessible. Additional questions deal with the respondent's citation and reference to data, their use of data journals in carrying out search and retrieval, and whether they have (co)authored a data paper or data article. The data was collected via SurveyMonkey3, where it remains stored along with a copy in .ods format in the DANS EASY Archive4. The reuse of the questions and data collected from the study in 2011 is likewise based on the same selection used to define the population of the earlier study. The data collected allows for insight into the changing attitudes and practices within GreyNet's research community and renders a use case for other research communities.